Application of anti-corrosion seepage-proofing agent in phosphate radical and fluorine ion environment

By adding corrosion-resistant anti-seepage agent to the concrete, the service life and durability of structures such as phosphogypsum library in phosphate and fluoride ion environments are solved, and the efficient corrosion resistance and durability of structures are improved in strong corrosion environments.

CN119430726APending Publication Date: 2025-02-14WUHAN XINJUTU TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411193241.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the service life and durability of structures such as phosphogypsum libraries in phosphate and fluoride ion environments, and the structures are easily damaged in strong corrosion environments, with high maintenance costs and no obvious effect.

Method used

Add corrosion-resistant anti-seepage agent to the concrete, including components such as activaters, antifreeze-thawing agents, retarders, surfactants, etc., and add them at 0.5 to 3% of the gelling material to resist the corrosion of phosphate and fluorine ions. .

Benefits of technology

By adding corrosion-resistant anti-seepage agent, the compressive strength of the concrete specimens is significantly improved in the phosphorus-fluorine environment, which can effectively resist acidic wastewater corrosion, extend the service life of the structure, and improve its durability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430726A_ABST
    Figure CN119430726A_ABST
Patent Text Reader

Abstract

The invention discloses an application of an anti-corrosion and anti-seepage agent in a phosphate radical and fluorine ion environment, which is characterized in that the anti-corrosion and anti-seepage agent is added into concrete according to 0.5-3% of a cementing material to prepare a required structure for resisting corrosion of phosphate radicals and fluorine ions. A concrete test piece added with the anti-corrosion and anti-seepage agent is in a phosphorus-fluorine acid environment for a long time, the compressive strength of the concrete test piece is still in an enhanced trend, the addition of the anti-corrosion and anti-seepage agent has the effect of resisting corrosion of phosphate radical and fluorine ion environment acid wastewater, and a concrete structure can still be very stable even in a strong acid environment; the high efficiency can provide a feasible solution for prolonging the service life of highly acidic environment structures such as ardealite storehouses and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to application of an anti-corrosion and anti-seepage agent in a phosphate and fluoride ion environment. Background Art

[0002] Wet-process phosphoric acid is mainly obtained by decomposing phosphate ore with sulfuric acid, and phosphogypsum is the waste residue produced in the process of wet-process phosphoric acid. At present, phosphogypsum is mainly treated by stockpiling. A large amount of stockpiled phosphogypsum contains a variety of harmful components, especially soluble impurities, such as water-soluble P2O5, unreacted sulfuric acid and F ions. These harmful components migrate and diffuse in the soil and groundwater, posing a huge threat to environmental safety. The initial dam of the phosphogypsum reservoir, flood discharge facilities and other major structures have been in a highly corrosive phosphorus-fluorine environment for a long time. Long-term immersion will seriously damage the structures, thereby shortening the service life of the structures. The later maintenance costs are very high, and the effect is not obvious. At present, there is no effective way to effectively increase the service life of structures in phosphorus-fluorine environments.

[0003] Therefore, an anti-corrosion and anti-seepage agent for use in phosphate and fluoride ion environments is urgently needed. Summary of the invention

[0004] In order to solve the defects of the prior art, the present invention provides an application of an anti-corrosion and anti-seepage agent in a phosphate and fluoride ion environment. The anti-corrosion and anti-seepage agent is added to concrete, and then the concrete specimens are immersed in acidic wastewater and concentrated acidic wastewater in a phosphate and fluoride environment for a certain period of time. Then the compressive strength of the specimens is tested, and the results are better than those of a blank control group to which no anti-corrosion and anti-seepage agent is added, indicating that the anti-corrosion and anti-seepage agent has excellent corrosion resistance and can be widely used in structures such as phosphogypsum depots that are in a strongly corrosive phosphate and fluoride environment for a long time, so as to solve the durability problem of the building in the early stage of design and construction, thereby filling the technical gap in this field.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] The invention provides an application of an anti-corrosion and anti-seepage agent in a phosphate and fluoride ion environment. The anti-corrosion and anti-seepage agent is added into concrete according to 0.5-3% of a cementitious material to prepare a required structure for resisting the corrosion of phosphate and fluoride ions.

[0007] Preferably, the anti-corrosion and anti-seepage agent comprises 5 to 15 parts by mass of an activator, 1 to 3 parts by mass of an antifreeze-thaw agent, 0.5 to 1.5 parts by mass of a retarder, 0.2 to 0.5 parts by mass of a surfactant and residual water.

[0008] Preferably, the activator includes at least one of aluminum sulfate, sodium sulfate, sodium carbonate, iron sulfate, calcium chloride and sodium hydroxide.

[0009] Preferably, the antifreeze-thaw agent includes at least one of urea, sodium nitrite, sodium chloride and sodium nitrate.

[0010] Preferably, the retarder includes at least one of sodium gluconate, ammonium metaborate, boric acid and ammonium borate.

[0011] Preferably, the surfactant includes at least one of fatty alcohol polyoxyethylene ether, isopropanolamide, and sodium dodecylbenzene sulfonate.

[0012] Preferably, the mass ratio of the concrete cementitious materials is water: cement: sand: stone: fly ash: mineral powder: polycarboxylic acid water reducer = 0.3-0.6: 0.6-1.5: 2.5-3.5: 2.6-3.5: 0.1-0.15: 0.15-0.3: 0.016-0.025.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] (1) The addition of inorganic salt components that play an exciting role in the anti-corrosion and anti-seepage agent produces a salt effect. When poured together with concrete, it can increase the ion concentration of the cement slurry solution, improve the solubility of hydrated minerals, and accelerate the cement hydration process.

[0015] (2) Sulfate-containing components react with calcium ions to generate calcium sulfate, which is more active than directly added calcium sulfate and further promotes the hydration reaction. Nano-scale active substances can combine with calcium ions and undergo complexation, precipitation and regeneration processes, hydrolyzing into colloidal hydroxide colloids, silica gel, etc., which accelerate the appearance of system crystals and promote / induce the formation of hydrated calcium silicate (gel), and cross-link crystallization and repair cracks at cracks to increase strength, increase gel, reduce porosity, and improve aggregate interface structure.

[0016] (3) After fluoride ions enter the internal structure of concrete, they react with calcium ions to form calcium fluoride precipitates that are insoluble in water. This not only stabilizes the fluoride ions, but also increases the strength of the concrete.

[0017] (4) After the soluble ions in the acidic wastewater penetrate into the concrete, the solubility of some cement hydration minerals can be reduced due to the common ion effect, and the cement hydration products crystallize and precipitate faster, thereby improving the early strength of the cement.

[0018] (5) The hydrophilic groups of the nano-active substances chemically bond with the substrate to repair surface damage, and due to the action of the hydrophobic ends, a dense hydrophobic protective film is formed to resist the penetration of internal and external ions or molecules, thereby improving its strength and impermeability, achieving the dual effects of building anti-seepage and enhancing the density of concrete.

[0019] In summary, the compressive strength of the concrete specimens added with the anti-corrosion and anti-seepage agent of the present invention is still enhanced when they are in a phosphorus-fluoride acidic environment for a long time. The addition of the anti-corrosion and anti-seepage agent has the effect of resisting the erosion of acidic wastewater in a phosphate and fluoride ion environment, and can make the concrete structure very stable even in a strong acidic environment. Its high efficiency can provide a feasible solution for improving the service life of structures in a strong acidic environment such as a phosphogypsum depot, so as to solve the durability problem of the building in the early stage of design and construction, and fill the technical gap in this field. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is an X-ray powder diffraction pattern of a crushed powder sample of a test piece to which 2% of an anti-corrosion and anti-seepage agent is added in the present invention. DETAILED DESCRIPTION

[0021] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0022] Example 1

[0023] 7 parts of aluminum sulfate, 2 parts of calcium chloride, 3 parts of sodium carbonate, 2 parts of sodium nitrite, 0.5 parts of sodium gluconate, 0.5 parts of fatty alcohol polyoxyethylene ether and 85 parts of water were mechanically stirred at room temperature until dissolved to prepare an anti-corrosion and anti-seepage agent.

[0024] Example 2

[0025] 5 parts of aluminum sulfate, 2 parts of sodium sulfate, 2 parts of calcium chloride, 3 parts of sodium carbonate, 2 parts of sodium nitrite, 0.5 parts of sodium gluconate, 0.5 parts of fatty alcohol polyoxyethylene ether and 85 parts of water were mechanically stirred at room temperature until dissolved to prepare an anti-corrosion and anti-seepage agent.

[0026] Example 3

[0027] 5 parts of aluminum sulfate, 2 parts of sodium sulfate, 2 parts of calcium chloride, 3 parts of ferric sulfate, 2 parts of sodium nitrite, 0.5 parts of sodium gluconate, 0.5 parts of fatty alcohol polyoxyethylene ether and 85 parts of water were mechanically stirred at room temperature until dissolved to prepare an anti-corrosion and anti-seepage agent.

[0028] Example 4

[0029] 7 parts of ferric sulfate, 2 parts of calcium chloride, 3 parts of sodium carbonate, 2 parts of sodium nitrite, 0.5 parts of sodium gluconate, 0.5 parts of fatty alcohol polyoxyethylene ether and 85 parts of water were mechanically stirred at room temperature until dissolved to prepare an anti-corrosion and anti-seepage agent.

[0030] Example 5

[0031] 5 parts of ferric sulfate, 2 parts of sodium sulfate, 2 parts of calcium chloride, 3 parts of sodium carbonate, 2 parts of sodium nitrite, 0.5 parts of sodium gluconate, 0.5 parts of fatty alcohol polyoxyethylene ether and 85 parts of water were mechanically stirred at room temperature until dissolved to prepare an anti-corrosion and anti-seepage agent.

[0032] Example 6

[0033] 7 parts of aluminum sulfate, 2 parts of calcium chloride, 3 parts of sodium carbonate, 2 parts of urea, 0.5 parts of sodium gluconate, 0.5 parts of fatty alcohol polyoxyethylene ether and 85 parts of water were mechanically stirred at room temperature until dissolved to prepare an anti-corrosion and anti-seepage agent.

[0034] Example 7

[0035] 7 parts of aluminum sulfate, 2 parts of calcium chloride, 3 parts of sodium carbonate, 2 parts of sodium nitrite, 0.5 parts of ammonium borate, 0.5 parts of fatty alcohol polyoxyethylene ether and 85 parts of water were mechanically stirred at room temperature until dissolved to prepare an anti-corrosion and anti-seepage agent.

[0036] Example 8

[0037] 7 parts of aluminum sulfate, 2 parts of calcium chloride, 3 parts of sodium carbonate, 2 parts of sodium nitrite, 0.5 parts of ammonium borate, 0.5 parts of sodium dodecylbenzene sulfonate and 85 parts of water were mechanically stirred at room temperature until dissolved to prepare an anti-corrosion and anti-seepage agent.

[0038] Application Example 1

[0039] A concrete specimen was prepared with a mass ratio of water: cement: sand: stone: fly ash: mineral powder: polycarboxylic acid water reducer = 0.57:1:2.85:3.1:0.169:0.23:0.024.

[0040] Application Example 2

[0041] During the preparation process of Application Example 1, the anti-corrosion and anti-seepage agent prepared in Example 1 was added according to 1% of the cementitious material to prepare a concrete specimen with the anti-corrosion and anti-seepage agent added.

[0042] Application Example 3

[0043] During the preparation process of Application Example 1, the anti-corrosion and anti-seepage agent prepared in Example 1 was added according to 1.5% of the cementitious material to prepare a concrete specimen with the anti-corrosion and anti-seepage agent added.

[0044] Application Example 4

[0045] During the preparation process of Application Example 1, the anti-corrosion and anti-seepage agent prepared in Example 1 was added according to 2% of the cementitious material to prepare a concrete specimen with the anti-corrosion and anti-seepage agent added.

[0046] The concrete specimens prepared in Application Examples 1 to 4 were cured at a humidity of 95% and a temperature of 20° C. for 28 days.

[0047] The concrete specimens cured for 28 days in Application Examples 1 to 4 were completely immersed in phosphorus-fluorine environment acidic wastewater and concentrated acidic wastewater for 30 days, 60 days, 90 days and 180 days, and the compressive strength of the specimens was tested.

[0048] The components of the acidic wastewater and concentrated acidic wastewater were tested by plasma chromatography, and the results are shown in Table 1.

[0049] Table 1: Composition of acidic wastewater and concentrated acidic wastewater.

[0050]

[0051]

[0052] As can be seen from Table 1, the PO4 3- With F - The content is higher than that of the original acidic wastewater, especially PO4 3- The content is about 2.52 times that of acidic wastewater. This is also the main reason why the pH value of concentrated acidic wastewater is much lower than that of acidic wastewater, indicating that concentrated acidic wastewater is more corrosive than non-concentrated acidic wastewater.

[0053] The specimens (blank group and experimental groups with different proportions of anti-corrosion and anti-seepage agents added) that had been immersed in acidic wastewater and concentrated acidic wastewater for 0, 30, 90 and 180 days were taken out and naturally placed for 1-3 days to dry before the compressive strength test. In order to test the accuracy of the results, three specimens under the same experimental conditions were tested in parallel, and then the average value was taken. The compressive strength of each specimen under different immersion days is shown in Table 2.

[0054] Table 2: Compressive strength results of each specimen after immersion for 0, 30, 90 and 180 days.

[0055]

[0056]

[0057] As can be seen from Table 2, in the non-concentrated acidic wastewater, when the soaking days were 0, 30, 90 and 180 days, the test groups with 1-2% anti-corrosion and anti-seepage agent added had higher compressive strength than the blank group, and the best performance was achieved when the addition amount was 1%. The same effect was achieved when the specimens were immersed in concentrated acidic wastewater, when the soaking days were 0, 30 and 180 days, that is, the compressive strength was higher than that of the blank group at the three addition amounts, and at this time, the best performance was achieved when the addition amount of anti-corrosion and anti-seepage agent was 2%.

[0058] In order to explore the anti-seepage and anti-cracking principle of anti-corrosion and anti-seepage agents, the changes in the chemical composition of the specimens under curing in acidic wastewater and concentrated acidic wastewater were analyzed from a microscopic perspective. Three specimens were placed in the air, immersed in non-concentrated acidic wastewater and concentrated acidic wastewater, and the fragments after compressive strength testing were collected. After grinding and mixing evenly, the powder samples were analyzed by X-ray powder diffraction. Figure 1 This is the X-ray powder diffraction pattern of the crushed powder sample of the test piece with 2% anti-corrosion and anti-seepage agent added. Figure 1 It can be seen that the specimens immersed in concentrated or non-concentrated acidic wastewater and the specimens placed in the air without immersion are all crystals, with abundant, sharp diffraction peaks and narrow half-height width. Compared with the unimmersed specimens, except for an additional peak with a 2θ angle of 11.6° belonging to C4AF in the concentrated immersion solution, the other peak positions and intensities of the three samples are completely consistent. This shows that the main substances contained in the three specimens are the same, and the main components of the specimens immersed in the tested solution are almost the same as those of the unimmersed specimens, indicating that the concrete specimens have good compactness and anti-seepage ability. Compared with the standard cards, the substances corresponding to 2θ are C3S (a), C2S (b), calcite (c), C3A (d), C4AF (e), quartz (f), gypsum (g), ferrite (h), wollastonite (i) and sodium calcium feldspar (j).

[0059] The present invention uses the acidic wastewater from the phosphoric acid workshops of four major phosphate fertilizer enterprises in Yichang, Hubei as the experimental medium source, mixes them according to their proportions to obtain unconcentrated acidic wastewater, adds corrosive medium sodium fluoride to the acidic wastewater, and then adjusts the pH to about 1.5 with 85% phosphoric acid, which is used as concentrated acidic wastewater. With cement, sand, stone, fly ash, and mineral powder as the main raw materials, under a certain mix ratio, an anti-corrosion and anti-seepage agent is added, and a 100×100×100 test piece is made in a mixing station and cured for 28 days. The changes in the quality and compressive strength of the test pieces after soaking in unconcentrated acidic wastewater and concentrated acidic wastewater for 30, 90 and 180 days were tested. The results show that compared with the control sample without the addition of the anti-corrosion and anti-seepage agent, after the test pieces with the addition of the anti-corrosion and anti-seepage agent were soaked in the acidic wastewater for 180 days, the concrete compressive strength of the three formula test pieces tested was increased by about 14-17MPa compared with that before soaking, which is better than the control group. Therefore, the anti-corrosion and anti-seepage agent developed by the present invention has the effect of improving the concrete's resistance to erosion by acidic wastewater in phosphorus and fluorine environments, and can effectively solve the problems of service life and durability of structures.

[0060] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. An application of an anti-corrosion and anti-seepage agent in a phosphate and fluoride ion environment, characterized in that: The anti-corrosion and anti-seepage agent is added into concrete at 0.5-3% of the cementitious material to prepare the required structure, which is used to resist the corrosion of phosphate and fluoride ions.

2. The use of an anti-corrosion and anti-seepage agent according to claim 1 in a phosphate and fluoride ion environment, characterized in that: The anti-corrosion and anti-seepage agent comprises 5 to 15 parts by weight of an activator, 1 to 3 parts by weight of an antifreeze-thaw agent, 0.5 to 1.5 parts by weight of a retarder, 0.2 to 0.5 parts by weight of a surfactant and residual water.

3. The use of an anti-corrosion and anti-seepage agent according to claim 1 in a phosphate and fluoride ion environment, characterized in that: The activator includes at least one of aluminum sulfate, sodium sulfate, sodium carbonate, iron sulfate, calcium chloride and sodium hydroxide.

4. The use of an anti-corrosion and anti-seepage agent in a phosphate and fluoride ion environment according to claim 1, characterized in that: The antifreeze-thaw agent includes at least one of urea, sodium nitrite, sodium chloride and sodium nitrate.

5. The use of an anti-corrosion and anti-seepage agent in a phosphate and fluoride ion environment according to claim 1, characterized in that: The retarder includes at least one of sodium gluconate, ammonium metaborate, boric acid and ammonium borate.

6. The use of an anti-corrosion and anti-seepage agent according to claim 1 in a phosphate and fluoride ion environment, characterized in that: The surfactant includes at least one of fatty alcohol polyoxyethylene ether, isopropanolamide, and sodium dodecylbenzene sulfonate.

7. The use of an anti-corrosion and anti-seepage agent in a phosphate and fluoride ion environment according to claim 1, characterized in that: The mass ratio of the concrete cementitious materials is water: cement: sand: stone: fly ash: mineral powder: polycarboxylic acid water reducer = 0.3-0.6: 0.6-1.5: 2.5-3.5: 2.6-3.5: 0.1-0.15: 0.15-0.3: 0.016-0.025.

Citation Information

Patent Citations

  • Low-alkali liquid accelerator and preparation method thereof

    CN112028522A

  • Anti-permeability and anti-crack concrete waterproofing agent and preparation method thereof

    CN112608063A